Evaluasi Kesejahteraan dan Kesehatan Satwa Liar yang Diperdagangkan di Bandar Lampung - Mhd Muhajir Hasibuan; Agung Yoga Pangestu; Oktarina Maulidia; Rizki Kurnia Tohir; Astri Aulia Suwanda; Dhinta Aurellia Sanjaya; Fajar Aditya Julyatmojo; Muhammad Hafidz; Ruben Josafat Sadatua Hutahaean; Yasyafri Evo (Wana Lestari, 2024)
Indonesia known for its high biodiversity, is home to various species of wildlife, with 17% of the world's wild animals found in its territory. However, this wealth makes Indonesia one of the major suppliers of both legal and illegal wildlife trade, which threatens conservation efforts. This study aims to identify the potential of wildlife trade, health factors, and the welfare of traded animals. Conducted in Bandar Lampung in February 2022, the research employed direct observation through structured interviews with pet shop owners, as well as document studies. The findings indicate that despite a post-pandemic decline, wildlife trade in the region still holds significant potential. Health factors, such as mouth ulcers in pythons and metabolic diseases in geckos, pose major challenges, although adequate care is provided in these shops. Animal welfare remains a critical concern, as dependence on wild-caught animals from the wild threatens their sustainability. This study emphasizes the importance of implementing sustainable management practices and adhering to existing regulations to ensure the continuity of wildlife trade in Indonesia